Enhancing learning through Interior Design in public high school classrooms in Quezon City - Sabulao, Mary Diane S.; Faustino, Johanna Victoria Acab (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT This research is an attempt to explore the role of interior design in the enhancement of learning process of students. Through a study of design considerations employed in the selected classrooms of the schools in the study the following were discussed: 1) layout of classrooms in terms of factors, namely space planning, lighting and ventilation, and materials and finishes used; 2) existing conditions of the classrooms in relation to students? academic performance; 3) comparison of the results among the three classrooms, and 4) concerns cited by the students and teachers in relation to improving the students? academic performance. Sense of Place and Territoriality were used as guiding theories of the research. Employing a qualitative research design, surveys, interviews, and photo documentation were conducted through non-probability quota sampling. High school students in selected classrooms of three public schools in Quezon City (School 1, School 2, School 3) were surveyed with a total of 120 survey respondents. From the results of interviews, teachers? perception on their students? academic performance, and the effectivity of their current classrooms were gathered. Findings show that the more the students? needs and preference were addressed in the design of the classroom, the more they tend to feel that their identity is reflected in the space. This territorial behavior leads to higher sense of belonging, making the students relate better to their teachers and classmates. The study has proven that good classroom attendance, desirable classroom perception, and active performance can be achieved through a symbiotic relationship between sense of place and territoriality in the classroom.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Classrooms -- Philippines